Pengembangan Bahan Ajar Pada Materi Pecahan Kelas IV Berbasis Pendekatan Open Ended dan Kemampuan Penalaran SD Negeri Gayamsari 02 Semarang - Chevi Anjarwati; Joko Sulianto; Mira Azizah (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2021)
The background that encourages this research is that the existing teaching materials do not support learning activities, which triggers the low ability of students' reasoning. This study aims to describe the use of teaching materials, describe the procedures for developing teaching materials, and test the appropriateness of expert and teacher validation teaching materials on fraction material for class IV based on an open-ended approach and reasoning skills in elementary schools. This study uses the Research and Development method, the data analysis technique used is descriptive qualitative, and the instrument is in the form of a content validation assessment questionnaire, construct, initial field trials. Data collection obtained from the results of the content validation, construct, and initial field trials at SD Negeri Gayamsari 02 Semarang. The results of the content validation phase I obtained a score of 77.3 good categories, stage II obtained a value of 85.6 very good categories. The results of the first stage construct validation obtained a value of 76.5 good criteria, the second stage obtained a value of 83.5 for very good criteria. The results of the initial field trial of content validation obtained a value of 81.9 good criteria and construct validation obtained a value of 89.1 very good criteria.